Bathymetric and tectonic consequences of plume interaction with the ocean floor - Watson, SJ (2018)
Most magmatism on Earth occurs in the ocean or along its margins, associated with plate boundaries and/or mantle plumes. The key surface expression of mantle plumes is mafic volcanism. Investigating the geomorphology, structure, petrology, geochemistry, and geochronology of plume products on the seafloor provides clues to their formation and evolution, leading to a better understanding of the responsible submarine and solid earth processes. Bathy metric maps provide the primary data source for observing and studying the seafloor. Global satellite-derived bathymetry maps are readily available and provide critical information regarding the dominant features in ocean basins, including mid-ocean ridges, transform faults/fracture zones, and large seamounts. However, satellite-derived bathymetry has a spatial resolution of ~10 - 20 km in areas not constrained by shipboard bathymetry, meaning finer-scale seafloor features have remained unresolved using this technique. Seafloor exploration of many smaller plume-related volcanic products is only now being realised, due to modern advances in the quality and resolution of ship-borne acoustic data and processing methods. This thesis investigates how seafloor processes influence the morphological development of small-scale oceanic plume products that have formed as a subsidiary of major LIP emplacement or due to ridge-plume interaction. I adopt a multidisciplinary approach to evaluate oceanic plume products in three tectonic settings: divergent (Perth Abyssal Plain), convergent (Ontong Java Plateau), and intraplate (Kerguelen Plateau). Each study area has been formed by, or interacted with, a mantle plume, providing insights into ongoing and past submarine processes. I show that unravelling the formation and evolution of complex seafloor features is enabled by modern multibeam echo sounder data, particularly when these data are combined with other co-located geoscientific datasets. Characterisation and classification of the first multibeam bathymetric data around two atolls atop the Ontong Java Plateau reveal widespread debris deposits formed through multiple phases of erosion and deposition (Chapter 2). The first multibeam bathymetric data around Heard and McDonald Islands on the Kerguelen Plateau show a province of elongated flat-topped sea knolls. Spatiotemporal patterns of sea knoll morphologies suggest non-uniform glacial influence across the area (Chapter 3). Bathymetric data and geochemical analyses from an extinct seafloor spreading centre offshore Western Australia suggest that both Cretaceous plate kinematics and likely episodic plume upwelling contributed to its unusual morphology and variable basaltic geochemistry (Chapter 4). My results demonstrate the capabilities of modern acoustic data and seafloor sampling when investigating the manifestation and evolution of oceanic plume products. Overall, I show that the geomorphology and nature of small-scale submarine plume products are strongly influenced by both tectonic setting and seafloor processes during and subsequent to their formation.